Integrasi Sains untuk Membangun Kesepahaman dan Toleransi dalam Mewujudkan Harmonisasi Masyarakat Multi Agama - Servasius Balok; Maria Montessori; Susi Fitria Dewi; Erianjoni (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the role of religious instructors in integrating science to build understanding and tolerance in realizing the harmonization of multi-religious communities in Tarutung District, North Tapanuli Regency. The research method used is a qualitative approach with in-depth interviews and observations. The results showed that religious educators act as communicators, motivators and role models in educating the community about the importance of tolerance and mutual respect. They also apply a science-based approach in the extension program to improve people's understanding of diversity. The main conclusion of this study is that the integration of science in religious counseling can strengthen interfaith relations and create a harmonious environment in the midst of diversity.